Detection of mycobacterial DNA in pleural fluid from patients with tuberculous pleurisy by means of the polymerase chain reaction: comparison of two protocols. Issue 4 (April 1992) - de Lassence, A; Lecossier, D; Pierre, C; Cadranel, J; Stern, M; Hance, A J
Abstract : BACKGROUND: The detection of mycobacterial DNA in clinical samples on the basis of the polymerase chain reaction is a promising approach for the rapid diagnosis of tuberculous infections. No consensus exists, however, about which protocols are most sensitive, and the usefulness of this approach in the diagnosis of tuberculous effusions has been assessed in few patients. METHODS: The sensitivity of two protocols was compared for the detection of DNA from Mycobacterium tuberculosis in samples containing known amounts of mycobacterial DNA and in DNA extracted from 15 tuberculous pleural effusions. The results obtained for pleural fluid have been compared with cytological findings and with results obtained by standard microbiological techniques. RESULTS: Mycobacteria could be detected by acid fast staining in none and by culture in three of the 15 pleural fluid samples. A protocol based on the detection of the IS6110 insertion element (which could detect one mycobacterial genome/sample reproducibly) gave a positive result in nine of the 15 tuberculous effusions, though some samples were only intermittently positive (p less than 0.05 compared with culture). In contrast, a protocol based on the detection of the gene coding for the 65 kD mycobacterial antigen (which could detect mycobacterial genomes only if there were at least 10/sample) gave a positive result in three of the 15 tuberculous effusions. Pleural fluid that was always positive with the amplification procedure detecting the IS6110 sequence contained more neutrophils (30% (SD 27%)) than samples that were intermittently positive or always negative (3% (3%)); mycobacterial DNA was never detected in the four samples containing less than 1% neutrophils. CONCLUSIONS: The amplification of the IS6110 insertion element represents a rapid and sensitive means of detecting M tuberculosis in tuberculous effusions. The enrichment of cells containing mycobacteria (possibly neutrophils) before DNA extraction may be required to improve the sensitivity of this approach.